Experimental and Theoretical Study on the Crack Defect Effect on the Bearing Capacity of a Rectangular Culvert - Wanqiong Wang; Shouhai Peng; Xiaolong Chen; Rongxi Mi; Qingqing Wu; Peng Zhang (Buildings)
Rectangular culverts are extensively employed in various municipal projects. Due to their frequent placement in weak strata within urban areas, these structures are susceptible to defects like cracks, which can significantly reduce their bearing capacity and even result in collapse or other failures. This study investigates the mechanical behavior of cracked rectangular culverts through laboratory tests, analyzing both the failure mechanisms and the impact of crack depth on the ultimate bearing capacity (UBC) of the culverts. Focusing solely on the effect of crack depth on the UBC of rectangular culverts with defects, this paper establishes fundamental assumptions and proposes a calculation method for the residual bearing capacity (RBC) of rectangular culverts under crack-induced conditions. The theoretical calculations closely align with the experimental results. The findings indicate that (1) the failure process of a rectangular culvert under trilateral normal external load can be categorized into the initial stage with no visible cracks, the crack progression stage, and the final failure stage; (2) the increase in crack depth leads to a decrease in the UBC of the rectangular culvert, indicating that cracks have a negative impact on its bearing capacity; and (3) when the crack depth reaches the protective layer’s thickness, the UBC of the rectangular culvert reduces by over 30%, providing further evidence that an increase in crack depth significantly diminishes its bearing capacity.